Covalent adaptable networks using boronate linkages by incorporating TetraAzaADamantanes - van Hurne, Simon; Kisters, Marijn; Smulders, Maarten M. J. (Frontiers in Chemistry, 2023)
Boronic esters prepared by condensation of boronic acids and diols have been widely used as dynamic covalent bonds in the synthesis of both discrete assemblies and polymer networks. In this study we investigate the potential of a new dynamic-covalent motif, derived from TetraAzaADamantanes (TAADs), with their adamantane-like triol structure, in boronic ester-based covalent adaptable networks (CANs). The TAAD-boronic ester linkage has recently been reported as a more hydrolytically stable boronic ester variant, while still having a dynamic pH response: small-molecule studies found little exchange at neutral pH, while fast exchange occurred at pH 3.8. In this work, bi- and trifunctional TAAD linkers were synthesised and crosslinked with boronic acids to form rubber-like materials, with a Young’s modulus of 1.75 MPa. The dynamic nature of the TAAD networks was confirmed by stress relaxation experiments, revealing Arrhenius-like behaviour, with a corresponding activation energy of 142 ± 10 kJ/mol. Increasing the crosslinking density of the material from 10% to 33% resulted in reduced relaxation times, as is consistent with a higher degree of crosslinking within the dynamic networks. In contrast to the reported accelerating effect of acid addition to small-molecule TAAD complexes, within the polymer network the addition of acid increased relaxation times, suggesting unanticipated interactions between the acid and the polymer that cannot occur in the corresponding small-molecules analogues. The obtained boronate-TAAD materials were thermally stable up to 150 °C. This thermal stability, in combination with the intrinsically dynamic bonds inside the polymer network, allowed these materials to be reprocessed and healed after damage by hot-pressing.